Prognosis of frail hospitalized COVID-19 patient: Better than expected? - Martial Coutaz; Julien Lagrandeur; Botturi Cecilia; Cohen Corinne (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2020)
Objective: To evaluate the characteristics and prognosis of hospitalized geriatric COVID-19-positive patients during the first 30 days of the Swiss confinement period. Design: A retrospective case series analyzing the characteristics and disease evolution for 81 patients admitted to the geriatric COVID-19-positive ward during a 30-day period from March 24 to April 22, 2020.  Setting and participants: Any COVID-19-positive patients who was admitted to one of four geriatric hospital sites who were >65 years old and did not desire intubation. Methods: Data collection on patients admitted throughout the study period, as well as chart review for those discharged within the 30-day period to ensure that information was complete. Results: We found a 61.5% survival rate among those in a unit with an average age of 84.4-years and a vulnerable to frail health status, among whom 62% were male. The clinical presentation of COVID-19 in this population was similar to that described among younger populations, including a predominance of respiratory symptoms, along with fever, myalgia, asthenia, and neurologic symptoms such as anosmia and ageusia, as well as bilateral pulmonary infiltrates on chest x-ray. Poor prognosis was strongly associated with higher oxygen demands, as well as higher fever and higher CRP and procalcitonin levels.  Conclusions: In spite of an average age of 84 years and a vulnerable to frail health status, the majority of patients in this geriatric COVID-19 ward survived to discharge. Regardless of frailty and underlying comorbidities, those who never developed severe oxygen demands were much more likely to survive. This study suggests that, among a vulnerable to frail geriatric patient cohort, the cumulative presence of inherent risk factors did not dictate prognosis. Future studies will allow us to elaborate which elements influence patients' oxygen demands, thereby permitting earlier interventions and improved prognosis.